Deep learning enabled smart mats as a scalable floor monitoring system - Qiongfeng Shi (Nature Portfolio, 2020)
Designing efficient and fast monitoring and response systems for smart building/home applications remains a challenge. Here, the authors propose a smart floor monitoring system developed through the integration of self-powered triboelectric sensing mechanism and deep learning data analytics.